ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KEPATUHAN MINUM OBAT PADA PASIEN TBC - Patoni, Asep Ahmad; Aisyiah, Aisyiah; Widowati, Retno (Coping: Community of Publishing in Nursing; Vol 11 No 3 (2023): Juni 2023, 2023)
Tuberculosis is an infectious disease that infects the body, especially the lungs caused by the Mycobacterium tuberculosis bacterium . Compliance with taking medication is very important in efforts to cure and reduce transmission. The prevalence of tuberculosis in Indonesia is a disease that causes a high number of morbidity and mortality. This study aims to determine the analysis of factors related to the level of medication adherence in TBC patients. The research methodology used in this study used cross-sectional . The sample of this research is 40 respondents using total sampling. The research instrument consisted of questionnaires about adherence to taking medication based on MMAS-8, patient knowledge, family support, support from health workers, and age. This questionnaire has been tested for validity and reliability with a cronbach's alpha coefficient of 0,468. Data analysis used Chi-square. The results of this study showed that out of 40 respondents there was no significant relationship between patient knowledge and the level of adherence to taking TB medication, p-value 0,869 (> 0,05), family support with a level of adherence to taking TB medication obtained p-value 0,119 (> 0,05), the support of health workers with the level of adherence to taking TB medication obtained p-value 0,234 (> 0,05) and age with a level of adherence to taking TB medication obtained p-value 0,112 (> 0,05).